BAHASA CINTA DALAM DUA BAHASA: PILIHAN BAHASA DALAM PERCAKAPAN KELUARGA MUDA DI PERKOTAAN BALI - A.A. Sg. Candra Permatasari (Journal of Innovation Research and Knowledge, 2025)
This study examines the language choices made by young parents in urban Bali in family conversations. Against Bali's unique sociolinguistic backdrop where Balinese with its speech level system (sor-singgih basa) interacts with Indonesian as the national language and English as a global language, this research aims to identify dominant language choice patterns and analyze the determining factors behind these choices. Using a qualitative approach with in-depth interviews and observations of ten young families in Denpasar, and drawing on Fishman's (1965) Domain of Language Use theory and Giles & Smith's (1979) Accommodation Theory, this study reveals three main patterns: domain-based patterns, one-person-one-language (OPOL) patterns, and dynamic code-mixing patterns. The findings indicate that language choice is not merely a pragmatic action but also a complex identity negotiation, driven by motivations to preserve cultural heritage, ensure children's social mobility, and manage impressions within extended families. This study concludes that young Balinese families serve as both agents of change and preservation in contemporary Balinese language ecology